Autonomous Flight of a Commercial Quadrotor - Curi, S. (2014)
In this paper we describe a controller and sensor fusion algorithm for a low-cost commercial quadrotor helicopter and its implementation in ROS. The dynamics of the system is assumed decoupled and identified as four SISO systems using subspace state-space system identification methods. A simple PD controller is designed using these open loop transfer functions and evaluated in simulation.